Effects of a flow perfusion conditions on the viability of cells seeded on anisotropic scaffolds - Semitela, Ângela (2019)
Articular cartilage is a highly organized tissue that it is adapted to the complex mechanical loading in joints. Given the limited self-healing abilities of this tissue, there is an increasing demand for tissue engineering approaches to develop successful cartilage replacements. However, it is difficult to mimic the biochemical and biomechanical microenvironment of the native tissue. Generally, tissue-engineered cartilage does not possess an anisotropic organization, particularly the collagen fibre alignment, which will induce a suitable cell response. The combination of electrospun scaffolds, cells and mechanical stimulation have been reported to develop tissue engineered cartilage with spatially-varying properties. Flow perfusion bioreactors have also been applied to enhance the formation and anisotropy of tissue engineered cartilage, as it imitates the physiological environment of the cartilaginous tissue. A series of anisotropic fibrous/porous electrospun scaffolds of polycaprolactone (PCL), gelatin, collagen and graphene oxide were developed, and their biocompatibility evaluated in static and perfused conditions. The results revealed that these scaffolds could not only allow cell adhesion, but also cell proliferation. The cell-seeded scaffolds subjected to flow perfusion displayed even higher cell viability, suggesting that the dynamic environment was beneficial to cell proliferation, and in the future, to the formation of tissue engineered cartilage.